2021
DOI: 10.1111/jce.14923
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term outcomes of index cryoballoon ablation or point‐by‐point radiofrequency ablation in patients with atrial fibrillation and systolic heart failure

Abstract: Catheter ablation is an established effective approach for the treatment of atrial fibrillation (AF) in patients with heart failure, however, the role of cryoablation in this setting is unclear. Procedural success and left ventricular systolic dysfunction (LVEF) improvement in patients with LVEF ≤ 45% undergoing index catheter ablation with cryoablation were evaluated. Freedom from AF recurrence was seen in 43% rising to 59% following repeat procedure. There were significant improvements in LVEF and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The quality assessment utilized the ROBINS‐1 tool to assess selection bias, confounding bias, intervention classification bias, incomplete outcome data, outcome measurement, and reporting bias. Four studies showed moderate overall bias, 16–18,20 while one was serious, 19 and the last one was critical 15 . Figure 2 shows the detailed quality assessment done on all the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality assessment utilized the ROBINS‐1 tool to assess selection bias, confounding bias, intervention classification bias, incomplete outcome data, outcome measurement, and reporting bias. Four studies showed moderate overall bias, 16–18,20 while one was serious, 19 and the last one was critical 15 . Figure 2 shows the detailed quality assessment done on all the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Pruszkowska et al 20 observed a significant reduction in the AF burden postprocedure in patients with HFrEF (18.5% vs. 52.9%; p = .001). Following a single CBA treatment, Prabhu et al 18 reported that 70% of patients maintained freedom from atrial arrhythmia recurrence over 12 months. A comparable early recurrence rate of atrial arrhythmia was identified among patient groups with no HF, HFpEF, HFmrEF, and HFrEF (16.2% vs. 15.4% vs. 14.9% vs. 12.2%, p = .798) 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent review [ 40 ] reported that, in the population of heart failure patients at functional stages I–III, catheter ablation decreases all-cause mortality and improves all-atrial arrhythmia recurrence rate as well as cardiac function when compared to medical management—findings are still inconclusive regarding the sickest heart failure patients, at functional stage IV. Focusing on CB ablation, long-term outcomes on functional stage and ejection fraction appear favorable and equivalent to those achieved with the RF-based approach [ 41 , 42 ].…”
Section: Patient Selection For Af Ablation Through Cryoablationmentioning
confidence: 99%
“…International Journal of General Medicine 2021:14 11 reported that an increase in the preoperative LAD and a long duration of AF were high-risk factors for AF recurrence following radiofrequency ablation. Prabhu et al 12 believed that the inner diameter of the left atrium might directly affect the ablation result, and patients with AF and a left atrium inner diameter >55 mm were likely to experience AF recurrence in the long term. Domestically, Kirchhof et al 13 reported that the sinus rhythm cardioversion rate following radiofrequency ablation was significantly higher in patients with AF of less than two years duration as compared with patients in AF for more than two years.…”
Section: Dovepressmentioning
confidence: 99%